Evaluasi Water Shut Off Dan Membuka Lapisan Baru Sumur Bagong Di Lapangan Lesma - Abdullah Rizky Agusman; Aly Rasyid; Dika Latief Lesmana (Department of Petroleum Engineering, 2022)
Evaluation of Water Shut Off and Opening a New Layer of the Bagong Well in the Lesma Field, In oil and gas exploitation activities at the Bg01 Well, the well has been in production for a long time, so there is a problem where the proportion of water content in production wells continues to increase. compared to the proportion of oil and gas content produced, the improvement is carried out using the water shut off method by closing the existing perforation holes and opening new perforations in the same layer. Or closing the existing perforation holes that are indicated to cause an increase in water and the production of other perforated parts. By closing the layer, it is hoped that the water cut will decrease so that it will increase oil and gas production.